The Inductiveness of Agricultural Village-Type Cluster Creation in Developing Countries - Lyudmila Ivanovna Petrova; Nadezda Yurievna Glubokova; Ravil Gabdullaevich Akhmadeev; Olga Alekseevna Bykanova; Elena Igorevna Artemova; Ramzil Borisovich Gabdulkhakov (ETIKONOMI, 2021)
The assessment of emerging risks is substantial risk in implementing and creating various types of clusters used in the agricultural sector of the economy. In this regard, the goal is to develop practical measures to ensure the creation of a cluster of an agricultural settlement at the regional level, taking into account various types of risk that directly affect its creation and development. The study revealed that within the framework of the policy of substitution for domestic production and marketing of agricultural products during the formation of a cluster, it would allow combining more into a standard established system from production, processing to the sale of finished agricultural products both at the local level and at the federal level. This approach will significantly harmonize the interests of all participants of the agroindustry, as well as significantly simplify and expand access to external export markets, thereby reducing the cost of marketing research. At the same time, clustering will increase the overall economic impact on individual farmers, which will have a more significant impact on the development of non-resource zonal territories employed to produce agricultural products. Therefore, it will affect the increase in jobs in small villages.JEL Classification: F63, O13, Q18How to Cite:Petrova, L. I., Glubokova, N. Y., Akhmadeev, R. G., Bykanova, O. A., Artemova, E. I., & Gabdulkhakov, R. B. (2021). The Inductiveness of Agricultural Village-Type Cluster Creation in Developing Countries. Etikonomi, 20(2), xx– xx. https://doi.org/10.15408/etk.v20i2.22014